2016
DOI: 10.3390/molecules21040477
|View full text |Cite
|
Sign up to set email alerts
|

Green Technique-Solvent Free Microwave Synthesis and Antimicrobial Evaluation of New Thiopyridine Arabinosides

Abstract: Abstract:A green protocol has been applied to synthesize a novel series of 3-cyano-2-(tri-O-acetyl-β-D-arabinopyranosylthio)pyridines in a short reaction time, in higher yields and with simpler operations, when compared with the conventional heating method. Deacetylation of the obtained acetylated arabinosides produced 2-(β-D-arabinopyranosylthio)-3-cyanopyridines. The structures of the obtained products were confirmed on the basis of spectroscopic data (FT-IR, 1D, 2D-NMR). The synthesized compounds were scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…All of these facts prove the importance of pyridine derivatives as promising bioactive agents. In addition, some pyridine-2(1 H )-one derivatives have been shown to be hopeful antineoplastic active agents for the treatment of cancers [15] and to possess potential activity against different microorganisms [16,17,18]. This guided us to prepare novel pyridine nucleoside analogues in solvent-free medium using microwave irradiation as an economic, fast, ecofriendly, and efficient method for getting these promising candidates.…”
Section: Introductionmentioning
confidence: 99%
“…All of these facts prove the importance of pyridine derivatives as promising bioactive agents. In addition, some pyridine-2(1 H )-one derivatives have been shown to be hopeful antineoplastic active agents for the treatment of cancers [15] and to possess potential activity against different microorganisms [16,17,18]. This guided us to prepare novel pyridine nucleoside analogues in solvent-free medium using microwave irradiation as an economic, fast, ecofriendly, and efficient method for getting these promising candidates.…”
Section: Introductionmentioning
confidence: 99%
“…Pyridine derivatives have attracted much attention because of their medicinal properties, such as antifungal, antibacterial, antiinflammatory, antiviral, and antitumor activities. [1][2][3][4][5][6][7] Furthermore, the benzoylation of these compounds may induce biological properties that makes it possible for ester group-containing compounds to act as prodrugs, and thus deliver the actual active group to the target biomolecule. 8,9 The coordination of these types of ligands to certain metals has also shown enhanced medicinal properties.…”
mentioning
confidence: 99%
“…Finally, Eldeab et al reported a solvent-free microwave irradiation method as a green technique for the synthesis of new thiopyridine arabinoses [18]. Moreover, the authors described the antimicrobial activity of all synthesized compounds against a panel of Gram-negative and Gram-positive bacterial strains.…”
mentioning
confidence: 99%